2013
DOI: 10.1039/c3cc46762g
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the membrane-disrupting and seeding properties of the TDP-43 amyloidogenic core

Abstract: The amyloidogenic core in the TAR DNA-binding protein (TDP-43) C-terminal fragment has been characterized with its chemical, biochemical, and structural properties delineated. Various properties of the core sequence, including membrane impairment ability and the seeding effect, have also been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 21 publications
0
34
0
1
Order By: Relevance
“…Since it has been shown that the addition of proline residues may block β-sheet propensity and prevent amyloidogenesis, various glycines were replaced by prolines in TDP-43 glycine-rich peptides (G294P, GGG294PPP, and GGG308PPP) to confirm the impact of proline substitutions in the peptide aggregation and cytotoxicity. While GGG294PPP was selected due to the frequent pathological mutations in residues 294 and 295, GGG308PPP was chosen for the amyloidogenic property in the specific region (residue 307–322) of TDP-43 [19]. Our result indicated the impact of pathological and de novo designed mutations in the amyloid formation and shed light on the possible peptide design in suppressing TDP-43 proteinopathy in the future.…”
Section: Introductionmentioning
confidence: 82%
“…Since it has been shown that the addition of proline residues may block β-sheet propensity and prevent amyloidogenesis, various glycines were replaced by prolines in TDP-43 glycine-rich peptides (G294P, GGG294PPP, and GGG308PPP) to confirm the impact of proline substitutions in the peptide aggregation and cytotoxicity. While GGG294PPP was selected due to the frequent pathological mutations in residues 294 and 295, GGG308PPP was chosen for the amyloidogenic property in the specific region (residue 307–322) of TDP-43 [19]. Our result indicated the impact of pathological and de novo designed mutations in the amyloid formation and shed light on the possible peptide design in suppressing TDP-43 proteinopathy in the future.…”
Section: Introductionmentioning
confidence: 82%
“…The aggregation propensity of TDP‐43 may be dependent on the region of the C‐terminal altered as the core aggregation sequences are in specific locations of the C‐terminus [165]. Using a number of recombinant TDP‐43 CTF peptides of the core aggregation sequence, one group were able to induce the formation of TDP‐43‐positive amyloid fibrils and seeding reactions in vitro and cell culture [166]. However, truncation beyond residues 317 were not able to induce amyloid fibrils and formed amorphous aggregates [166].…”
Section: Introductionmentioning
confidence: 99%
“…Using a number of recombinant TDP‐43 CTF peptides of the core aggregation sequence, one group were able to induce the formation of TDP‐43‐positive amyloid fibrils and seeding reactions in vitro and cell culture [166]. However, truncation beyond residues 317 were not able to induce amyloid fibrils and formed amorphous aggregates [166]. Therefore, residue‐specific post‐translational modifications to this region may be the pathogenic event leading to a pathological TDP‐43 amyloid formation and templated seeding reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the specific nature of TDP-43 aggregates from patient histopathological samples is a topic for discussion (1, 18 -20), the prion-like progressive behavior of TDP-43 proteinopathies (21)(22)(23)(24) suggests that these aggregates have a seeding capacity characteristic of amyloids. Consistent with this notion, recent studies have revealed that the isolated LCD (13) and many of its fragments (25)(26)(27)(28)(29)(30)(31) readily form amyloid fibrils, whereas deletion of or within this region abrogates fibrillation (32)(33)(34). However, little is known about the mechanism of this amyloidogenic pathway.…”
mentioning
confidence: 97%